SIRT1 relieves Necrotizing Enterocolitis through inactivation of Hypoxia-inducible factor (HIF)-1a. Issue 16 (17th August 2020) - Bai, Ming; Lu, Chaoxiang; An, Lu; Gao, Qi; Xie, Weike; Miao, Feng; Chen, Xiaofeng; Pan, Yongkang; Wang, Qi
ABSTRACT: Necrotizing enterocolitis (NEC) is a major cause of mortality and morbidity in newborns, characterized by inflammatory intestinal necrosis. Sirtuin-1 (SIRT1), a NAD-dependent deacetylase, is involved in multiple biological functions. It has been reported that SIRT1 was downregulated in NEC tissues. However, the precise role of SIRT1 in NEC progress remains unknown. In this study, we found that SIRT1 was decreased in serum samples of NEC patients, associated with an inflammation response. an in vitro model was established by using LPS-induced NEC-like cell in this study. The results indicate that overexpression of SIRT1 inhibited the cell apoptosis induced by LPS. Besides, overexpression of SIRT1 suppressed the high expression of proinflammatory factors (IL-6, IL-8, and TNF-α), the decrease of transepithelial electrical resistance (TEER), and the decline expression of tight junction proteins (ZO-1, ZO-2, and Claudin-4) induced by LPS in Caco-2 cells. What is more, serum HIF-1α was increased in NEC patients. SIRT1 overexpression suppressed the expression and activity of HIF-1a, while knockdown of SIRT1 made the opposite effect. In summary, this study indicates that overexpression of SIRT1 alleviates the inflammation response and intestinal epithelial barrier dysfunction through regulating the expression and inactivation of HIF-1a.